RELATIONSHIP OF THE SIZE AND LOCATION OF THE TYMPANIC MEMBRANE PERFORATION IN CHRONIC SUPPURATIVE OTITIS MEDIA WITH THE MAGNITUDE OF HEARING LOSS - Rasouli, Abdul Azeem; Zhapar, Kurban (Interdisciplinary Approaches to Medicine, 2022)
Chronic suppurative otitis media is a severe health condition that affects people worldwide. Perforation in the tympanic membrane reduces the surface area of the membrane available for sound transmission. It’s important to identify and treat tympanic membrane perforation as soon as possible, since untreated tympanic membrane perforation contributes to chronic disruptive changes in the middle ear, resulting in further hearing loss, which is a major physical and psychological issue that affects people’s lives. The study has been conducted to compare the relationship between the location and size of perforation of the tympanic membrane in chronic suppurative otitis media with the magnitude of hearing loss. The cross-sectional prospective study was conducted among 67 patients who visited the Otorhinolaryngology department for myringoplasty. The study period was from January to April 2021, the age group of patients was between 8 and 43 years old. The number of female participants was 35 (52.2%) and males – 32(47.8%) respectively. Average age ±SD was 21.93±9.47 years. Fifty (74.6%) patients had right ear perforation and seventeen (25.4%) with left ear perforation/ It was not statistically significant (χ2=22.891; p-value=0.290). Most of the patients were with subtotal of (all quadrants) 30 (44.77%), 2-3 quadrants, and one quadrant perforation were 23 (34.32%) and 14 (20.89%) respectively. Most of the patients, i.e.37 (55.22%), had hearing loss between 26-40dB. There was a significant connection between the perforation size and degree of hearing, (χ2=22.891; p-value <0.0001). In one quadrant perforation, greatest hearing loss was on the post inferior quadrant 29.97±4.32 dB. For 2-3 quadrants perforation the hearing loss was greatest in postero-superior combined with postero-inferior perforation 37.42±9,59dB. The most significant hearing loss was in subtotal perforation mean ±SD was 42.13±7.07dB. Hearing loss increases in proportion to the extent of the perforation, post inferior quadrant alone and combined with the post-super were observed with the greatest hearing loss according to the findings of this study.